The preparation and characterisation of chromatin from third instar larvae of Drosophila melanogaster - Andrews, Peter W. (1974)
A procedure is described for the isolation of large amounts of chromatin from Drosophila third instar larvae. This material is suitable for immunisation of rabbits, and preliminary analysis by immunodiffusion reveals little cross reaction between chromatin and cytoplasm antigens, using antisera prepared against them. In addition to these studies, results from an examination of the exchange of radioactively labelled cytoplasmic proteins with nuclei suggest that no more than 5% of the total chromatin protein is of cytoplasmic origin. Electrophoretic analysis indicates that of this 5%, 20% migrates as a single band, in the same position as f2b histone. The techniques of radioactively labelling larvae which were used, may be suitable for achieving specific activities of up to 100μC/mg larval protein. Contamination of the chromatin by yeast proteins from the larval food is no more than 10%. Of this 30% is represented by one electrophoretic band. Immunological analysis reveals little cross reaction with yeast extracts. Electrophoretic and amino acid analyses of the chromatin proteins confirm earlier reports concerning Drosophila histones.